2001
DOI: 10.1084/jem.194.10.1485
|View full text |Cite
|
Sign up to set email alerts
|

CD8β Endows CD8 with Efficient Coreceptor Function by Coupling T Cell Receptor/CD3 to Raft-associated CD8/p56lck Complexes

Abstract: The extraordinary sensitivity of CD8+ T cells to recognize antigen impinges to a large extent on the coreceptor CD8. While several studies have shown that the CD8β chain endows CD8 with efficient coreceptor function, the molecular basis for this is enigmatic. Here we report that cell-associated CD8αβ, but not CD8αα or soluble CD8αβ, substantially increases the avidity of T cell receptor (TCR)-ligand binding. To elucidate how the cytoplasmic and transmembrane portions of CD8β endow CD8 with efficient coreceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
184
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(199 citation statements)
references
References 42 publications
14
184
1
Order By: Relevance
“…In contrast, transfer of the CD8-dependent TCR into CD8b-deficient lymphocytes revealed that transduced T cells did not respond to antigen stimulation even at high antigen concentration, indicating that CD8a/a homodimers were unable to provide any co-receptor function. This highlighted that the CD8b chain played a central role in co-receptor function, consistent with previous studies with T cell hybridomas showing that CD8a/b heterodimers were more efficient co-receptors than CD8a/a homodimers [11,16]. It is possible that the physiological role of CD8a/a does not include co-receptor function for MHC class I-restricted TCR, but may be required for the formation of memory T cells, although this issue remains controversial, and for the function of intra-epithelial lymphocytes in the gut [17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, transfer of the CD8-dependent TCR into CD8b-deficient lymphocytes revealed that transduced T cells did not respond to antigen stimulation even at high antigen concentration, indicating that CD8a/a homodimers were unable to provide any co-receptor function. This highlighted that the CD8b chain played a central role in co-receptor function, consistent with previous studies with T cell hybridomas showing that CD8a/b heterodimers were more efficient co-receptors than CD8a/a homodimers [11,16]. It is possible that the physiological role of CD8a/a does not include co-receptor function for MHC class I-restricted TCR, but may be required for the formation of memory T cells, although this issue remains controversial, and for the function of intra-epithelial lymphocytes in the gut [17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…Although C terminus of CD8␣ is associated with tyrosine kinase p56lck, responsible for TCR phosphorylation during T cell activation, palmitylation of CD8␤ is essential for recruitment into lipid raft (25,48). Our results, demonstrating the differential capacity of CD8-binding vs CD8-null tetramers to stain CTL, highlight the importance of CD8 ectodomains in facilitating Ag recognition by acting as a bona fide T cell adhesion molecule.…”
Section: Discussionmentioning
confidence: 59%
“…Although CD4 molecules do not enhance the stability of pMHC-TCR interactions (23,24), the effects of CD8 remain controversial in surface plasmon resonance (SPR) studies (14,23,25,26). Structural and kinetic analysis of CD8 binding to MHC class I molecules has clarified the molecular motifs involved (26,27).…”
mentioning
confidence: 99%
“…Furthermore, the BIAcore binding experiments involving soluble reagents of pMHC, TCR and CD8 or CD4 do not indicate any direct binding of the TCR with CD8 or CD4, or enhancement by CD4 or CD8 to the binding of TCR-pMHC (19)(20)(21). However, one early study demonstrated some enhancement of TCR-pMHC binding in the presence of soluble CD8 using BIAcore analysis (16).…”
Section: Help Of Co-receptors Cd8/cd4 To the Peptide-mhc/tcr Bindingmentioning
confidence: 99%
“…Binding dynamics and complex structures have shed light on this complex interactions for a single ligand (pMHC) recognized simultaneously by two receptors, both abTCR and co-receptor CD8 or CD4 (15)(16)(17)(18)(19)(20)(21).…”
Section: Help Of Co-receptors Cd8/cd4 To the Peptide-mhc/tcr Bindingmentioning
confidence: 99%